2005
DOI: 10.1080/02841860500218819
|View full text |Cite
|
Sign up to set email alerts
|

Does electron and proton therapy reduce the risk of radiation induced cancer after spinal irradiation for childhood medulloblastoma? A comparative treatment planning study

Abstract: (2005) Does electron and proton therapy reduce the risk of radiation induced cancer after spinal irradiation for childhood medulloblastoma? A comparative treatment planning study, Acta Oncologica, 44:6, 554-562,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 44 publications
2
77
0
1
Order By: Relevance
“…The risk of radiation-induced secondary cancer in children with cholangiocarcinoma treated with RT was also found to be the highest after X-ray therapy, and the lowest after intensive proton therapy (69). The increased risk of coronary artery disease and valvular dysfunction was found to be associated with cardiac irradiation during X-ray treatment of Hodgkin's lymphoma (70,71).…”
Section: Pbt For Different Cancersmentioning
confidence: 82%
“…The risk of radiation-induced secondary cancer in children with cholangiocarcinoma treated with RT was also found to be the highest after X-ray therapy, and the lowest after intensive proton therapy (69). The increased risk of coronary artery disease and valvular dysfunction was found to be associated with cardiac irradiation during X-ray treatment of Hodgkin's lymphoma (70,71).…”
Section: Pbt For Different Cancersmentioning
confidence: 82%
“…This is a relevant issue as there seems to be a potential doubling of late secondary cancers due to increased integral doses in areas outside the target when using multiple fields in IMRT [12,13]. Recently a treatment planning study indicated much lower lifetime risk for secondary cancer after proton therapy compared with IMRT, but the risk for IMRT was particularly high in children with medulloblastoma [14]. I could not find any specific publications addressing secondary cancer after proton therapy, despite that 43.000 patents have been exposed to this treatment modality [1].…”
Section: Olav Dahlmentioning
confidence: 99%
“…The irregular and sometimes complex shape of the target volume in H&N and breast, and all OARs in the surrounding are probably the reasons for the improvements. For target volumes located in or abutting the spinal cord [11,12] the changes in the dose distribution between the three techniques show large variations and no general conclusion can be drawn due to the limited number of data. In the pelvic region the data also varies and no clear difference in the dose distribution between the three techniques is seen.…”
Section: Comparison Of Treatment Planning Studiesmentioning
confidence: 99%
“…The maximum dose in the different OARs for conventional technique is much higher than for the other techniques. For proton beams the data varies to a large extent and no general conclusion can [9] Hypopharynx Parotid 3DCRT, protons (scanned) 5 Pirzkall et al [56] mainly H&N Spinal cord 3DCRT 9 Lomax et al [52] H&N Several organs Standard photons, protons (scanned) 4 Lomax et al [53] Breast Lung, heart Protons (scanned) 1 Johansson et al [51] Breast Lung, heart Standard, protons (scanned) 11 Cella et al [8] Prostate Rectum 3DCRT, protons (scanned) 1 Mock et al [54] Prostate Rectal wall 3DCRT, protons (passive) 5 Aoyama et al [49] Prostate Rectal wall 3DCRT, tomotherapy 5 Johansson et al [50] Rectal ca Small bowel 3DCRT, protons (scanned) 16 Lomax et al [52] Pelvic Several organs Standard photons, protons 4 Weber et al [12] Paraspinal Several organs Protons (scanned) 5 Mu et al [11] Spinal Several organs 3DCRT, protons (scanned) 5…”
Section: Dose Distribution In Target Volumementioning
confidence: 99%